СТРУКТУРА І СЕЗОННА ДИНАМІКА ФІТОКОМПОНЕНТИ БІОКОСНОЇ СИСТЕМИ МОРСЬКОГО ГІПЕРСОЛОНОГО ОЗЕРА НА МИСІ ХЕРСОНЕС (КРИМ) - Празукін, О. В.; Бобкова, А. Н.; Євстигнєєва, І. К.; Танковская, І. Н.; Шадрін, М. В. (Marine Ecological Journal, 2023)
Structure and dynamics of vegetation and its biochemical composition in small shallow hypersaline lake in the Crimea were studied during two years (May 2004 – April 2006). Salinity in the lake fluctuates from 15.5 to 202 ‰ in time and space, temperature from -0.7 to 43.6oC. There are 5 species of macrophytes (Cladophora vadorum, C. siwachensis, Ulothrix implexa, Rhizoclonium tortuosum, Ruppia cirrhosa) forming mats in the lake. C. vadorum dominates. There are two kinds of mats, namely floating and bottom ones. Highest biomass was observed in July – August (3.0 – 5.5 kg/m2), in winter – spring – 0.2 – 1.0 kg/m2. The mats have laminated structure; the layers have some differences in color and biochemical composition.